Prevalence of Mycobacterium avium subspecies paratuberculosis and hepatitis E in New World camelids in Austria. (7th July 2017) - Stanitznig, A.; Khol, J. L.; Lambacher, B.; Franz, S.; Kralik, P.; Slana, I.; Vasickova, P.; Wittek, T.
Abstract : Mycobacterium avium subspecies paratuberculosis (MAP) is the causative agent of paratuberculosis in domestic ruminants and New World Camelids (NWC). Hepatitis E virus (HEV) is an important public health concern worldwide. The virus has been identified in several species, some of them serving as a reservoir for zoonotic HEV strains. Husbandry and breeding of llamas and alpacas have increased in Austria in recent years. Therefore, the aim of the present study was to evaluate the prevalence of MAP and HEV in NWC in Austria. Altogether 445 animals, originating from 78 farms were enrolled in the study. Of the animals sampled, 184 (41.35%) were llamas and 261 (58.65%) were alpacas. 443 blood samples for MAP‐ELISA and 399 faecal samples for quantitative PCR (qPCR) and culture for MAP as well as for HEV detection by RT‐qPCR have been collected. All of the 399 animals tested for shedding of MAP were negative by faecal solid culture. Using qPCR, 15 (3.8%) of the animals were MAP positive and 384 (96.2%) negative. Out of the 443 serum samples examined for specific antibodies against MAP by ELISA, 6 (1.4%) were positive, 1 (0.2%) was questionable and 436 (98.4%) samples were negative. All faecal samples were tested negative for HEV.